La Rivoluzione russa nella riflessione dei comunisti tedeschi. Un controcanto - Vaccaro, Giovambattista (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
In the position of the German communists in the Twenties years towards the October revolution the first positive judgment has been followed by a harsh criticism which extended also to Lenin and to some sides of the thought of Marx himself. Some intellectuals as Pannekoek, Korsch, Rühle, Bloch reproached the Russian revolution for its mainly political character and its exclusive interest for economic transformations which produced a state capitalism ruled by a bureaucracy which exercised its power as a class opposed to the proletariat itself . By this way in these intellectuals’ opinion the Russian revolution missed the aim of a communist revolution: life transformation in consideration of liberation and realization of Man. Keywords: Russian revolution; Pannekoek; Korsch; Rühle; Bloch.